Experiment based comparative analysis of stator current controllers using predictive current control and proportional integral control for induction motors - Vo Thanh Ha; Tran Trong Minh; Nguyen Tung Lam; Nguyen Hong Quang (Bulletin of Electrical Engineering and Informatics, 2020)
The stator current control loop plays an important role in ensuring the quality of electric drives interm of producing fast and adequate required torque. When the current controller provides ideal responses, speed control design subsequently is in charge of improving the system performances. Classical PID control is commonly used in current loop design, this paper presents the comparative analysis of current stator controller using proportional integral control and predictive current control (PCC) in field-oriented control-based induction motor drives, with rigidly coupled loads. The experimental results show system responses with PID and PCC. Informative experiment-based analysis provides primary guidance in selection between the two controls.